2014
DOI: 10.1084/jem.20130301
|View full text |Cite
|
Sign up to set email alerts
|

Pro-inflammatory human Th17 cells selectively express P-glycoprotein and are refractory to glucocorticoids

Abstract: Inflammatory T helper 17 cells in humans are distinguished by selective expression of MDR1 and are enriched in the gut of patients with Crohn’s disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
407
0
13

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 399 publications
(439 citation statements)
references
References 56 publications
(125 reference statements)
19
407
0
13
Order By: Relevance
“…demonstrated, in CD patients, a MDR1 enrichment within Th1.17 that resist to GC treatment. 61 On the contrary, MDR1 loss of function was identified in a subset of patients with an aggressive form of ileal CD. 78 Therefore, MDR1 role is dual in this pathology.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…demonstrated, in CD patients, a MDR1 enrichment within Th1.17 that resist to GC treatment. 61 On the contrary, MDR1 loss of function was identified in a subset of patients with an aggressive form of ileal CD. 78 Therefore, MDR1 role is dual in this pathology.…”
Section: Introductionmentioning
confidence: 99%
“…In healthy subjects, among CD4 + memory T cells, MDR1 delineates a subset of effector T cells (Teff) mainly composed of Th1.17 also called pathogenic Th17. 61 Moreover, our team recently characterized, in human, the CD73 + Teff population that is particularly enriched in Th1.17 and expressed higher MDR1 levels than their CD73 neg counterpart. 62 A recent study also suggests that MDR1 is also selectively expressed by Teff bearing the lectin-like receptor CD161.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence supports the concept of a SR Th17 phenotype, and their adoptive transfer, or the overexpression of their canonical transcription factor retinoid-related orphan receptor (ROR)-γt, has been shown to induce SR disease in a murine model of asthma (12,13). In humans, glucocorticoid-resistant Th17 cells express the multidrug resistance type 1 protein, which is inhibited by cyclosporine A (CsA) (14), and historically CsA was one of the first drugs used to successfully rescue SR diseases (1). We therefore hypothesized that CsA would selectively inhibit human Th17 cells.…”
mentioning
confidence: 99%
“…P-glycoprotein, for example, is under the influence of PXR, FXR, NFκB and AP-1 pathways (Miller, 2010), but examination of co-regulated transcripts using pathway analysis tools may help determine the specific pathway that is active (Krämer et al, 2014). It has been demonstrated that microbial-derived compounds including indole metabolites can function as PXR ligands (Venkatesh et al, 2014) which have functions in other cell types such is the case with P-glycoprotein expressed in phagocytes and T cells (Ramesh et al, 2014;Cory et al, 2016).…”
Section: Alternative Alterations To Absorptionmentioning
confidence: 99%